Patient-Reported Chronic Pain Outcomes After Lung Transplantation. (March 2020) - Klinger, Rebecca Y.; Cunniff, Claire; Mamoun, Negmeldeen; Cooter, Mary; Hashmi, Nazish; Hopkins, Thomas; Smith, Patrick; Hartwig, Matthew; Bottiger, Brandi
Chronic pain after lung transplantation is a significant concern, in particular given the heterogeneity of the patient population and the challenges of achieving adequate pain control amid concerns related to complex immunosuppressant regimens and the possibility of respiratory depression. We undertook a patient-reported outcomes (PRO) survey administered via our electronic health care portal to examine the postoperative incisional pain prevalence in a cohort of lung transplant recipients at a single, high-volume center where bilateral thoracosternotomy is the preferred surgical approach. The Patient Reported Outcomes Measurement Information System (PROMIS) Global Health and Pain Intensity short forms were sent to a total of 173 lung transplant recipients who were more than 2 months postsurgery at the time of the study. A total of 64 patients responded to both PROMIS surveys (response rate 38%). In the cohort of survey respondents, we observed a chronic pain incidence of 58% after lung transplantation (median pain score 1/10) and an overall good quality of life score (median score 4/5); however, only 9.4% reported moderate-severe pain (pain score ≥5/10). Survey nonrespondents had higher rates of pretransplant opioid and psychiatric medication use compared with respondents. In this study, we demonstrated the feasibility of using an electronic PRO survey for assessing postoperative pain outcomes after lung transplantation. However, measuring pain outcomes using this type of tool highlights issues of response rate and potential selection bias. Larger studies are needed to adequately assess the risk and predictors of chronic pain after lung transplantation and its impact on quality of life.